Improving transitions in care for children with complex and medically fragile needs: a mixed methods study - Janet A. Curran; Sydney Breneol; Jocelyn Vine (BMC, 2020)
Abstract Background Children with medical complexity are a small yet resource intensive population in the Canadian health care system. The process for discharging these children from hospital to home is not yet optimal. The overall goal of this project was to develop recommendations to be included in a provincial strategy to support transitions in care for children with complex and medically fragile needs. Methods A wide assortment of stakeholders participated in this mixed method, multiphase project. During Phase 1, data was gathered from a range of sources to document families' experiences transitioning from an inpatient hospital stay back to their home communities. In Phase 2, pediatricians, nurses, and health administrators participated in key stakeholder interviews to identify barriers and facilitators to a successful transition in care for children and families with complex care needs. A multi-sector consensus meeting was held during Phase 3 to discuss study findings and refine key recommendations for inclusion in a provincial strategy. Results Six case studies were developed involving children and families discharged home with a variety of complex care needs. Children ranged in age from 15 days to 9 years old. Nine telephone interviews were conducted in Phase 2 with pediatricians, nurses, and administrators from across the province. A variety of inter-institutional communication challenges were described as a major barrier to the transition process. A consistent message across all interviews was the need for improved coordination to facilitate transitions in care. The consensus meeting to review study findings included physicians, nurses, paramedics, senior administrators, and policy analysts from different health and government sectors and resulted in six recommendations for inclusion in a provincial strategy. Conclusions This project identified policy and practice gaps that currently exist related to transitions in care for children with complex and medically fragile needs and their families. Our collaborative patient-centred approach to understanding how children and families currently navigate transitions in care provided a foundation for developing recommendations for a provincial wide strategy.